Flow channel design for metallic bipolar plates in proton exchange membrane fuel cells: Experiments. (15th October 2018) - Qiu, Diankai; Peng, Linfa; Yi, Peiyun; Lai, Xinmin; Lehnert, Werner
Highlights: Design and fabrication of BPP is further introduced based on our previous study. Round corner and clearance of moulds play important role in maximum channel height. Channel dimensions are selected by formability model and reaction efficiency. Channel height, channel thickness and effect of blank holder are discussed. Performance of single cell and short stack is tested to evaluate method reliability. Abstract: This study offers an efficient design method of flow channels of metallic bipolar plates (BPPs) to improve manufacturing technique of BPPs and maximize power density in proton exchange membrane (PEM) fuel cells. Stamped thin metallic BPPs with anticorrosive and conductive coating are promising candidates for replacing conventional carbon-based BPPs. Nevertheless, unlike carbon-based BPPs, the flow channel design of metallic BPPs should take into account not only the reaction efficiency, but also formability due to the possible rupture of the metallic channel during the micro-forming process. In our previous study, a forming limit model was first proposed to predict the maximum allowable channel height by the forming process. This study is conducted to further propose the method of the design and fabrication of metallic BPPs based on the numerical model. In order to determine channel geometry design from formability perspective, response surface method is utilized to build a formability model. Combining the formability model and reaction efficiency, flow field design for metallic BPPs (channel width of 0.9 mm, rib width of 0.9 mm, channel depth of 0.4 mm and radius of 0.15 mm) is proposed. Experiments on BPP fabrication and assembled 20-cell fuel cell testing are conducted to observe forming quality of micro channel and output performance on the real fuel cell. It is shown that the stamping force grows with increasing channel depth in a nonlinear manner and a blank holder is needed to eliminate the sheet wrinkle in the forming process. The uniformity of the voltage distribution in the 1000 W-class stack further proves the reliability of metallic BPPs designed by our method. The methodology developed is beneficial to the fabrication management of metallic BPPs and effective supplement to the channel design principle for PEM fuel cells.